Cryptocurrency And Environmental Sustainability: A Narrative Review From A Financial Management Perspective - Muhammad Imam Taufik; Muhammad Rijal Alim Rahmat (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
: Bitcoin’s rise as a decentralized digital asset has been accompanied by serious concerns over its environmental impact. This paper examines Bitcoin’s energy consumption, carbon emissions, and environmental footprint from a financial management perspective, emphasizing the implications for ESG risk, capital allocation, and sustainability disclosure. Employing a structured literature review, this study synthesizes 2023–2024 research on Bitcoin’s environmental damages and evaluates technological and policy mitigation strategies. Findings show Bitcoin’s annual energy use exceeds 130–175 TWh, contributing to over 90 MtCO₂ emissions, with substantial reputational and financial risks for firms involved. Policy responses including bans, taxation, and mandatory disclosure are shaping the crypto ecosystem. From a financial standpoint, Bitcoin’s sustainability performance increasingly affects investment access, cost of capital, and long-term viability. This research urges financial managers to actively mitigate and disclose crypto-linked environmental risks. Building on these findings, the paper further highlights how Bitcoin-related environmental externalities are no longer peripheral issues but have become material financial risks that must be integrated into strategic decision-making. Institutional investors, lenders, and asset managers are increasingly incorporating climate-related metrics into portfolio evaluation, thereby intensifying scrutiny of crypto-exposed firms. The study also discusses how ESG-oriented regulations and global climate commitments amplify pressure on financial institutions to reassess their exposure to energy-intensive digital assets. Moreover, advances in renewable energy adoption, efficiency improvements in mining hardware, and shifts in consensus mechanisms are evaluated as partial mitigation pathways, though their financial feasibility remains uneven.